Tác động của bất ổn năng lượng tới ô nhiễm không khí: Bằng chứng quốc tế và khuyến nghị cho Việt Nam - Lê Hải, Trung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study evaluates the impact of energy-related uncertainty on air pollution in both the short run and the long run. Utilizing the newly developed energy-related uncertainty index (EUI) of Dang et al. (2023), which specializes in capturing uncertainties arising from the energy market, this study explores the time-varying impacts of EUI on CO2 emissions in the short and the long run. In particular, our empirical analysis with a panel dataset spanning 27 countries from 2000 to 2023 reveals that energy-related uncertainty exacerbates air pollution in the short run but mitigates CO₂ emissions in the long run. This pattern may arise from shifts in energy consumption behaviors among households and firms, or represent an unintended consequence of reduced consumption and investment stemming from concerns over risks in the energy market. Building on these insights, the authors propose several policy recommendations aimed at stabilizing the energy market and enhancing the national energy structure.